DEVELOPMENT OF E-LEARNING OF MATHEMATICS NUMERACY TO IMPROVE STUDENTS' NUMERACY ABILITY - Reza Muhamad Zaenal; Sofhian Fazrin Nasrullah; Evan Farhan Wahyu Puadi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
When compared to reading and science skills, Indonesian students' numeracy skills always receive the lowest average scores. On the PISA test, 71% of students do not meet the minimum numeracy competency level. Because education and technological advancement are inseparable, a technology-based initiative that can improve students' numeracy skills is required. The creation of an e-learning numeracy application known as